Anatomic mapping of the internal spermatic vein via subinguinal varicocelectomy with intraoperative vascular Doppler ultrasound. Issue 2 (February 2019) - Juho, Yu-Cing; Wu, Sheng-Tang; Kao, Chien-Chang; Meng, En; Cha, Tai-Lung; Yu, Dah-Shyong
Abstract : Background: Varicocele is believed to be a dilated vein of the pampiniform plexus along the spermatic cord. Surgical treatment should be considered in men with a symptomatic varicocele. To date, microsurgical varicocelectomy is the most effective method among various varicocelectomy techniques, according to the current evidence. This study aimed to evaluate the effectiveness of subinguinal varicocelectomy with intraoperative vascular Doppler for symptomatic varicocele and map the distributional trend of spermatic content simultaneously. Methods: A total of 24 male patients underwent subinguinal varicocelectomy with intraoperative vascular Doppler ultrasound between March 2016 and October 2017, because of symptomatic varicocele or infertility. The numbers, sizes, and location of spermatic vessels in each site were recorded during operation. The visual analogue scale (VAS) score of scrotal pain was also obtained before and after surgery. Results: The mean number of spermatic veins that were ligated in each spermatic unit was 4.70 (±2.06). The predominant distributional zone of spermatic veins was the medial upper zone on an axial view of the spermatic cord. Fifty-six (44.1%) spermatic veins were found in this zone. Normally, each spermatic cord has 1.33 (±0.61) spermatic arteries. The average VAS score prior to surgery was 1.95 (±0.89) and it decreased to 0.05 (±0.21) after the surgery. Complete resolution of pain was observed in almost all symptomatic patients (95.23%). A significant positive relationship between the number of veins ligated and improvement of VAS score was also noted ( p < 0.05). Conclusion: Subinguinal varicocelectomy with intraoperative vascular Doppler ultrasound is an effective treatment for symptomatic varicocele. The more the internal spermatic veins are ligated, the more the VAS scores are improved. Determining the distributional trend of spermatic content is of great importance in the prevention of iatrogenic injury to the spermatic vessels and vas deferens.